Konsep Gaya Gravitasi Temuan Al-Biruni untuk Pembelajaran Kelas XI di Jenjang Pendidikan Madrasah - Syaepudin, Muhammad Rully; Naluri, Ratna; Irawan, Irawan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
The concept of gravity is the work of al-Biruni (973-1048 M / 362-H) Muslim scientists, but the work is claimed as Newton's findings (1642-1727 AD). This paper aims to reveal the facts it can be used as teaching materials in the madrasah Physics, with adjustments in accordance with the level of educational unit. This research uses qualitative method with historical approach of philosophy of science with Islamic perspective. Data were collected through literature study. The results showed that Newton was influenced by al-Biruni in terms of the concept of gravitational force. Al-Biruni made an important contribution to the measurement of the specific gravity of various substances with careful and accurate calculations. This concept is in accordance with the basic principle that he believes that all objects are attracted by the force of gravity of the earth. This theory was the gateway to Newton's laws 500 years later. These findings can be taught in madrasas through demonstration methods and experiments that are sociologically and anthropologically closed to madrasah culture